Populist parties in Europe : agents of discontent? - Kessel, Stijn van (Palgrave Macmillan, 2015)
Machine generated contents note: -- 1. Introduction: Studying Populism in European Party Systems -- 2. Populist Parties in 31 European Countries -- 3. Paths to Populist Electoral Success and Failure: fsQCA Analysis -- 4. Populist Parties in the Netherlands -- 5. Populist Parties in Poland -- 6. Populist Parties in the United Kingdom -- 7. Conclusion: Populist Parties and their Electoral Performance